PEMIKIRAN & KONTRIBUSI MUHAMMAD AL-BAQIR ( 56-114 H ) DALAM TATANAN EKONONOMI ISLAM - Fathan Mun'im (Al-Maslahah : Jurnal Ilmu Syariah, 2015)
One of unforgettable tabi’in scholar who made contribution in designing logo and small change of Islamic money was Imam Muhammad al-Baqir bin Ali Zainal Abidin bin Hussein. This writing is aimed at showing his merits and contributions that were written in Islamic history. It also describes brief biography of Imam Muhammad al-Baqir and exposes scholars’ opinion toward his thought in the Muawiyah dynasty age. He reformed economy and urged people to apply Islamic economy principles. He always reminded Muslims to be careful in trading their money because it is only means of worship.